Species richness and dispersion patterns of Lepidoptera (Rhopalocera) in the Nuraksa Forest Park, Lombok, Indonesia - MOHAMMAD LIWA ILHAMDI; AGIL AL IDRUS; DIDIK SANTOSO; GITO HADIPRAYITNO; MUHAMMAD SYAZALI; ISMAWAN HARIADI (Society for Indonesian Biodiversity, 2024)
Abstract. Ilhamdi ML, Idrus AA, Santoso D, Hadiprayitno G, Syazali M, Hariadi I. 2023. Species richness and dispersion patterns of Lepidoptera (Rhopalocera) in the Nuraksa Forest Park, Lombok, Indonesia. Biodiversitas 25: 62-70. Butterflies play an important role in maintaining the balance of ecosystems and pollinators. This study aims to analyze the species richness and dispersion patterns of butterflies from the Rhopalocera suborder in this area. The field survey was carried out from January to July 2023. The sampling site was divided into six areas. Specimens that were successfully collected using a hand net were identified at the Biological Laboratory of Mataram University. During this survey, 1576 specimens of Rhopalocera were recorded. This number consists of 47 species. Several species, such as Junonia atlites Linnaeus, 1763, Junonia almana Linnaeus, 1758, Danaus genutia Cramer, 1779, Hypolimnas misippus Linnaeus, 1764, and Amathusia phidippus Linnaeus, 1763 were found to be new records in the Nuraksa Forest Park area. The habitat types with the highest number of species are the utilization block and the traditional block, with 47 species. The habitat type with the lowest number of species is a special block with only 15 species. However, the highest species richness was found in the protection block, with an R-value of 8.09. The most dominant species is Leptosia nina Fabricius, 1793, and the least dominant is A. phidippus. Each species depicted a varying distribution in the six habitat types. According to the analysis results, it was found that the dispersion pattern of all Rhopalocera species is clustered. The research results themselves contribute to conservation and ecotourism efforts.